Patient Preferences and Concerns Regarding Stoma Formation Versus Sphincter-Sparing Surgery in Rectal Cancer : Stoma Formation Versus Sphincter-Sparing Surgery in Rectal Cancer - Shah, Farrukh Ozair; Abbasi, Hussain Jan; Raza, Tilal Ahmad; Imtiaz, Hajra (Pakistan Journal of Health Sciences, 2026)
The outcome of the decision between stoma construction and sphincter-sparing procedures is critical to the quality of life of the patients after a rectal cancer operation. In a socio-culturally diverse society like Pakistan, clinical outcomes are significant to the surgeon to reach a decision, but the views of the patients are significant as well. Objectives: To assess the preferences and concerns of rectal cancer patients regarding permanent stoma formation versus sphincter-preserving surgery in Khyber Pakhtunkhwa (KPK), Pakistan. Methods: This analytical cross-sectional study was carried out in the Department of General Surgery, Hayatabad Medical Complex, Peshawar, between January 2022 and December 2024. A total of 250 patients with rectal cancer were enrolled. The final analysis included 220 patients after excluding those who had undergone previous surgery (n=12), cognitive impairment (n=8), recurrent rectal cancer (n=6), and those who refused participation (n=4). Results: Among 220 respondents, 63.6% preferred sphincter-sparing surgery and 36.4% preferred abdominoperineal resection (APR). Female gender (p<0.069), rural residence (p=0.024), and a high concern level (p<0.001) were significant predictors of preference for APR, while knowledge of stoma was associated with lower odds of APR preference (p<0.012). Higher education (p=0.165) and age (p=0.271) were not statistically significant. Conclusions: Psychosocial, informational, and demographic factors all affect patient preferences for rectal cancer surgery. Patients with greater preoperative concerns, female gender, and those who lived in rural areas were all linked to a stoma favor. However, prior experience with stoma care was protective of this choice.